Lavender Exosome-Like nanoparticles attenuate UVB-Induced Photoaging via miR166-Mediated inflammation and collagen regulation - Sixu Li; Fei Liu; Song Zhang; Xin Sun; Xiaojing Li; Qiulin Yue; Le Su; Suzhen Yang; Lin Zhao (Scientific Reports)
Abstract Excessive UVB exposure accelerates skin aging by triggering inflammatory responses and collagen degradation. In recent years, plant-derived extracellular vesicles (PDEVs) have attracted considerable attention for their ability to encapsulate and deliver bioactive molecules, showing therapeutic potential in various fields such as skin care, wound healing, immune regulation, cancer therapy, and drug delivery. In this study, we isolated lavender exosome-like nanoparticles (LELNs) and evaluated their protective effects against UVB-induced skin photoaging. LELNs were purified using differential and sucrose density gradient centrifugation, with characterization through dynamic light scattering (DLS), nanoparticle tracking analysis (NTA), and transmission electron microscopy (TEM). UVB-induced photoaging models were established in HaCaT cells and mice. Treatment with LELNs reduced inflammatory cytokine levels (IL-1β, IL-6, TNF-α) in cell culture supernatants and mouse dorsal skin homogenates. Histopathological staining revealed significant improvements in epidermal thickness, collagen preservation, and overall skin integrity. Through high-throughput small RNA sequencing and transfection of miRNA mimics analysis, we identified key miRNAs in LELNs, particularly cpa-miR166e and zma-miR166h-3p, both of which belonged to the miR166 family and played a critical role in regulating inflammation and collagen metabolism. Functional enrichment analysis indicated that these miRNAs in LELNs were involved in DNA repair, oxidative stress response, and collagen synthesis pathways. Our findings highlight the potential of LELNs as a novel, natural therapeutic strategy for preventing and treating UVB-induced skin photoaging, offering insights into the use of plant-derived extracellular vesicles in dermatological applications.